PENGEMBANGAN SUMBER DAYA MANUSIA PEMERINTAHAN DESA DALAM TEKNIS PEMBUATAN SURAT KEPUTUSAN DI KABUPATEN INDRAMAYU - Gunardi Gunardi; Rasji Rasji (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
The village government has the duty and authority to regulate and manage village government affairs. The goal is that the village government is able to carry out village government affairs well, so that the village government can create the welfare of the village community. Likewise, the village government in Indramayu Regency is obliged to carry out these duties and authorities. One of the important aspects that must be possessed by village government officials is their ability to make various decisions related to the implementation of their duties and authorities and to solve various problems they face. The village government in Indramayu Regency still does not understand technically the correct and appropriate decision making in accordance with applicable regulations. What are the efforts to develop village government human resources so that they are technically able to make decisions properly and correctly? That is the problem that the village government needs to overcome through community service activities with the theme